Smart traffic light / Che Wan Azizul Che Wan Izhar - Che Wan Izhar, Che Wan Azizul (2010)
A smart traffic light which is intelligent, environmental friendly, safe and can reduce the problems is designed. The smart traffic light is basically designed to overcome any trespassing or reckless during the red signal. The traffic light consist a sensor, electronic device and a single camera which is control by a program come from MATLAB software. The function of the camera is to trigger the video when the car passes through it in red condition. Whenever the traffic light turns to red, the sensor will be activating automatically. When the car pass through the traffic light, the sensor will be turn on and the camera will record the car motion in a video format. The video and audio is then saving in the hardisk. The video is converting to the Microsoft wave before it will be send to the authorities using email. The sending process will be done using an electronic device like a cell phone. The program is basically design to detect the car motion when they pass the camera. The camera will detect the actual frame and capture the video. If any frame changes occur the camera will detect it as a motion of a target. To make the traffic light effective the sound detector which is located in program is eliminated to make sure no sound trouble disturbing the system. Therefore the only motion of the unwanted car will be record as prove of gaffe. The program consists of a setting of camera and the instruction to trigger the video.